Disentangling Excimer Emission from Chiral Induction in Nanoscale Helical Silica Scaffolds Bearing Achiral Chromophores. Issue 3 (4th November 2022) - Álvaro‐Martins, Maria João; Garcés‐Garcés, José; Scalabre, Antoine; Liu, Peizhao; Fernández‐Lázaro, Fernando; Sastre‐Santos, Ángela; Bassani, Dario M.; Oda, Reiko
Abstract: The synthesis and characterization of diketopyrrolopyrroles and perylenemonoimidodiesters linked to a substituted benzoic acid in the ortho, meta, and para positions, are reported. Grafting of these dyes on the surface of chiral silica nanohelices is used to probe how the morphology of the platform at the mesoscopic level affects the induction of chiroptical properties onto achiral molecular chromophores. The grafted structures are weakly (diketopyrrolopyrroles) or strongly (perylenemonoimidodiesters) emissive, exhibiting both locally‐excited state emission and a broad, structureless emission assigned to excimers. The dissymmetry factors obtained using circular dichroism highlight optimized supramolecular organization between the chromophores for enhancing the chiroptical properties of the system. In the ortho ‐ derivatives, poor organization due to steric hindrance is reflected in a low density of chromophores on walls of the silica‐nanostructures (<0.1 vs. >0.3 and up to 0.6 molecules/nm 2 for the ortho and meta or para derivatives, respectively) and lower g abs values than in the other derivatives ( g abs <2×10 −5 vs 6×10 −5 for the ortho and para derivatives, respectively). The para derivatives presented a better organization and increased values of g abs . All grafted chromophores evidence varying degrees of excimer emission which was not found to directly correlate to their grafting density. Abstract : Grafting fluorescent dyes onto chiral macroscopic objects can lead to chiral induction and the formation of excimers. Are these two related? Let′s find out!